Prevalence of diagnostically-discrepant Clostridioides difficile clinical specimens: insights from longitudinal surveillance - Anwar, Farhan; Clark, Marielle; Lindsey, Jason; Claus-Walker, Rachel; Mansoor, Asad; Nguyen, Evy; Billy, Justin; Lainhart, William; Shehab, Kareem; Viswanathan, V. K.; Vedantam, Gayatri (Frontiers in Medicine, 2023)
Background Clostridioides difficile Infection (CDI) is a healthcare-associated diarrheal disease prevalent worldwide. A common diagnostic algorithm relies on a two-step protocol that employs stool enzyme immunoassays (EIAs) to detect the pathogen, and its toxins, respectively. Active CDI is deemed less likely when the Toxin EIA result is negative, even if the pathogen-specific EIA is positive for C. difficile. We recently reported, however, that low-toxin-producing C. difficile strains recovered from Toxin-negative (‘discrepant’) clinical stool specimens can be fully pathogenic, and cause lethality in a rodent CDI model. To document frequency of discrepant CDI specimens, and evaluate C. difficile strain diversity, we performed longitudinal surveillance at a Southern Arizona tertiary-care hospital. Methods Diarrheic stool specimens from patients with clinical suspicion of CDI were obtained over an eight-year period (2015–2022) from all inpatient and outpatient Units of a > 600-bed Medical Center in Southern Arizona. Clinical laboratory EIA testing identified C. difficile-containing specimens, and classified them as Toxin-positive or Toxin-negative. C. difficile isolates recovered from the stool specimens were DNA fingerprinted using an international phylogenetic lineage assignment system (“ribotyping”). For select isolates, toxin abundance in stationary phase supernatants of pure cultures was quantified via EIA. Results Of 8,910 diarrheic specimens that underwent diagnostic testing, 1733 (19.4%) harbored C. difficile. Our major findings were that: (1) C. difficile prevalence and phylogenetic diversity was stable over the 8-year period; (2) toxigenic C. difficile was recovered from 69% of clinically Tox-neg (‘discrepant’) specimens; (3) the six most prevalent USA ribotypes were recovered in significant proportions (>60%) from Tox-neg specimens; and (4) toxin–producing C. difficile recovered from discrepant specimens produced less toxin than strains of the same ribotype isolated from non-discrepant specimens. Conclusion Our study highlights the dominance of Toxin EIA-negative CDI specimens in a clinical setting and the high frequency of known virulent ribotypes in these specimens. Therefore, a careful reevaluation of the clinical relevance of diagnostically-discrepant specimens particularly in the context of missed CDI diagnoses and C. difficile persistence, is warranted.